PUBLIC DEBT AND TAXES AS A FINANCIAL INSTRUMENTS OF THE BUDGET OF THE STATE POLICY: AN ANALYSIS OF KEY CONCEPTS - D. A. Smirnov (Гуманитарные и юридические исследования)
In this article the basic concepts of the foreign public debt is analyzed in relation to tax under different economic schools. The author considers scientific theories of the content of public debt in the context of relationship with the characteristic essence of taxes. On the basis of the study concluded that a variety of approaches to the subject of public debt by representatives of different scientific schools of financial law. The discussions between their representatives indicate that the active work of the scientific thought in the field. The absence of community and common scientific position in the views of scientists on this concept. It is noted that public debt is opposed to taxes when deciding on the financing of the budget deficit.